Study on Wear Characteristic of Rolling Bearing Caused by Rolling-sliding Motion - Zhongyang Li; Xinyu Pang; Zongqing Yan; Lei Zhang (Jixie chuandong)
Rolling-sliding motion is a special motion form which leads to the failure of rolling bearings. In order to study the wear characteristics of rolling bearings under rolling-sliding motion， the method of combining simulation with experiment is adopted. Firstly， Abaqus finite element software is used to establish the finite element simulation model of rolling bearing under rolling-sliding state， the dynamic response of friction force is obtained. Then， the friction data of the bearing in the process of motion are obtained through the rolling wear test bed. By using the Gray Correlation Analysis method，it is concluded that the correlation between the simulation data and the experiment data reached more than 0.8. Therefore，the friction obtained by simulation could be used as the basis to judge the changes of bearing wear state. In the bearing wear experiments， the particle size in the oil is detected and the surface topography of inner ring is recorded. The results show that the change of friction force obtained by simulation affects the change of oil particle size and surface morphology. The increase of particle number in oil and the wear mark on the inner ring surface are the wear results caused by the change of friction force. The positive feedback to the friction force makes its amplitude increase continuously， which further aggravates the wear of the bearing. The method of combining simulation with experiments provides the basis for the analysis and research of the bearing wear characteristics at each point under rolling-sliding state.